Garra mondica, a new species from the Mond River drainage with remarks on the genus Garra from the Persian Gulf basin in Iran (Teleostei: Cyprinidae) - Sayyadzadeh, Golnaz; Esmaeili, Hamid Reza; Freyhof, Jörg (Zootaxa, 2015)
Garra mondica, new species, from the Mond River drainage in Iran is distinguished from its congeners by having 7½ branched dorsal-fin rays; the breast, belly and back in front of the dorsal-fin origin naked and 9+8 branched caudal-fin rays. Garra mondica is also distinguished from all other congeners in the Persian Gulf basin, except an unidentified species from the Kol River, by having two fixed, diagnostic nucleotide substitutions in the mtDNA COI barcode region. The identity of G. gymnothorax, a nominal species from the Karun River drainage, and G. crenulata, a nominal species from Central Iran, are discussed. Garra populations examined from the Karun have a unique mtDNA COI barcode sequence, but their diagnostic characters are not consistent with the description and syntypes of G. gymnothorax. G. crenulata is considered as a synonym of G. rufa. Two populations of Garra from the Kol River have a sequence of the COI barcode region very similar to G. mondica, but cannot be identified as G. mondica and their identity cannot be resolved here.